Social Support, Social Skills, and Social Adjustment among New Santriwati - Siti Ainul Ma'rifah; Effy Wardati Maryam (Program Studi bimbingan Konseling PPs UNM Makassar, 2022)
This study aims to examine the relationship between social support, social skills, and social adjustment among new santriwati at Pesantren Bidayatul Hidayah in Mojokerto. This study was a correlational quantitative research. The subjects of this study were new santriwati at Pesantren Bidayatul Hidayah Mojokerto with a total population of 123 santriwati. Data were collected using Social Support Scale, Social Skill Scale, and Social Adjustment Scale with the reliability of 0.798 each. Based on the results of multiple regression analysis of 123 subjects, it was found that there is a relationship between social support, social skills, and social adjustment among new santriwati with the Sig. F count of 35.541 with the level of Sig. F of 0.000. The F count value was greater than the F table of 3.07 and the Sig. F value was lower than 0.05. 35.541 the level of Sig. F of 0.000. The F count value was greater than the F table of 3.07 and the Sig. F value was lower than 0.05.